2020
DOI: 10.1007/s00167-020-06275-z
|View full text |Cite
|
Sign up to set email alerts
|

No differences in clinical outcomes or isokinetic performance between cruciate-substituting ultra-congruent and posterior stabilized total knee arthroplasties: a randomized controlled trial

Abstract: Purpose Whether ultra-congruent (UC) or posterior cruciate ligament-stabilized (PS) inserts should be used in posterior cruciate ligament (PCL)-sacriicing total knee arthroplasty (TKA) remains debatable. Therefore, the aim of this prospective randomized controlled study was to compare the isokinetic performance and clinical outcomes of these inserts in PCLsacriicing TKA. Methods Sixty-six patients diagnosed with primary knee osteoarthritis were randomly assigned to either the UC or the PS group. There were no … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 28 publications
2
15
0
Order By: Relevance
“…Three recent RCT’s have reported no difference in outcomes between PS and CS designed TKA. Specifically, Akti et al found no significant differences in KSS or isokinetic performance scores between prosthesis designs [ 7 ]. Furthermore, two of these RCT’s have demonstrated no difference in functional outcomes or ROM intra-operatively, at 1 [ 24 ] and 5-year follow-up [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Three recent RCT’s have reported no difference in outcomes between PS and CS designed TKA. Specifically, Akti et al found no significant differences in KSS or isokinetic performance scores between prosthesis designs [ 7 ]. Furthermore, two of these RCT’s have demonstrated no difference in functional outcomes or ROM intra-operatively, at 1 [ 24 ] and 5-year follow-up [ 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…ROM 112.2° SF-36 physical 42.3 OKS 42 UCLA 4 Intra-op. ROM 115.1° SF-36 physical 37.9 OKS 41 UCLA 4 Akti (2021) [ 7 ] RCT 33 (fixed) 33 PS (fixed) Vanguard 1 year ROM 128.7° KSS ‘no difference’ ROM 133.9° KSS ‘no difference’ Hinarejos (2021) [ 30 ] RCT CS Triathlon* (29) CS U2** (30) PS Triathlon* (29) PS U2** (29) Triathlon and U2 1 year ROM* 112.8° ROM** 109.3° KSS total* 171.5 KSS total** 172.2 ROM* 116.5° ROM** 113.5° KSS total* 178.1 KSS total** 169.7 Kim (2021) [ 31 ] RCT 50 (fixed) 50 PS (fixed) Persona 2 years ROM 126.5° WOMAC 14.3 KSS function 110.8 KSS pain 52.2 ROM 127.4° WOMAC 14.5 KSS function 108.5 KSS pain 51.2 Han (2020) [ 18 ] RCT 34 (fixed) 34 PS (fixed) Triathlon 5 years ROM 115° Knee society knee 95 ROM 124° Knee society knee 93 Stirling (2019) [ 32 ] Retrospective cohort 54 (fixed) 364 CR (fixed) Triathlon 1 year Pain VAS 64.5 OKS 33.2 Pain VAS 70.6 OKS 34.6 Jang (2019) [ 20 ] RCT 45 (fixed) 45 PS (fixed) Vanguard 2 years ROM 130.1° KSS 157.1 WOMAC 27.1 129.9° KSS 156.5 WOMAC 26.6 Song (2017) [ 33 ] RCT 38 (fixed) 38 CR (fixed) e.motion 3 years ROM 130.8° HSS 94.3 WOMAC 25.2 KS Knee Society 92.3 ROM 128.7° HSS 93.0 WOMAC 24.0 KS Knee Society 89.6 Fritzsche (2017) [ …”
Section: Discussionmentioning
confidence: 99%
“…Song et al reported no differences in mediolateral or anteroposterior laxity between UC TKA and CR TKA in stress radiographs at full extension, and concluded that UC inserts can be a good option in TKA without bony box cuts when the PCL is damaged during an operation [50]. Moreover, UC TKA is a safe alternative to PS TKA and similarly has good clinical outcomes if cruciate substitution is necessary in randomized control trials and propensity score-matched analyses [46,51,52]. Furthermore, the joint perception and isokinetic performance were similar between UC TKA and PS TKA [52,53].…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…Moreover, UC TKA is a safe alternative to PS TKA and similarly has good clinical outcomes if cruciate substitution is necessary in randomized control trials and propensity score-matched analyses [46,51,52]. Furthermore, the joint perception and isokinetic performance were similar between UC TKA and PS TKA [52,53]. However, with the use of a navigation system intraoperatively, UC TKA was found to have more sagittal laxity with less femoral rollback and knee flexion than PS TKA [53][54][55].…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…10 Drawbacks to PS knees include additional bone resection for the cam and post mechanism, which increases the risk of condylar fracture. 11 In addition, post failure and patellar clunk syndrome 12 are also potential drawbacks.…”
Section: Introductionmentioning
confidence: 99%